2018
DOI: 10.1002/smll.201802053
|View full text |Cite
|
Sign up to set email alerts
|

Tolerogenic Iron Oxide Nanoparticles in Type 1 Diabetes: Biodistribution and Pharmacokinetics Studies in Nonobese Diabetic Mice

Abstract: Nanoparticle (NP) administration is among the most attractive approaches to exploit the synergy of different copackaged molecules for the same target. In this work, iron oxide NPs are surface-engineered for the copackaging of the autoantigen proinsulin, a major target of adaptive immunity in type 1 diabetes (T1D), and 2-(1'H-indole-3'-carbonyl)-thiazole-4-carboxylic acid methylester (ITE), a small drug conditioning a tolerogenic environment. Magnetic resonance imaging (MRI) combined with magnetic quantificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…They were be found in specific organs or regions with monocytes accumulation, especially the aorta of atherosclerosis model mice, through in vivo imaging system (IVIS) imaging and MRI 101 . MNPs co‐packaging of the autoantigen proinsulin, gained preferential accumulation in the pancreatic inflammatory zone and enhanced kidney elimination, which were used as potential MRI contrast agents for early diagnosis of Type 1 diabetes 102 . MNPs wrapped with vesicles derived from MSCs achieved effective targeting therapies for spinal cord injury 103 .…”
Section: Mnps Application In Other Diseasesmentioning
confidence: 99%
“…They were be found in specific organs or regions with monocytes accumulation, especially the aorta of atherosclerosis model mice, through in vivo imaging system (IVIS) imaging and MRI 101 . MNPs co‐packaging of the autoantigen proinsulin, gained preferential accumulation in the pancreatic inflammatory zone and enhanced kidney elimination, which were used as potential MRI contrast agents for early diagnosis of Type 1 diabetes 102 . MNPs wrapped with vesicles derived from MSCs achieved effective targeting therapies for spinal cord injury 103 .…”
Section: Mnps Application In Other Diseasesmentioning
confidence: 99%
“…As the size of the particles decreases, the magnetic properties of the iron(III) oxides exhibit peculiar properties, which differ from those of bulk counterpart materials, because of nanoscale confinement and surface effects. They have a range of practical applications in different technological areas, such as solar cell, pigment, microwave absorption, catalysis, environ-ment protection, gas sensor, magnetic storage, clinical diagnosis and treatment, etc [31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that $85% of Zn is distributed in the bone and muscle, and about 11% in the skin and the liver, while the remaining is distributed in other tissues [38]. However, target organs for NPs can be different, since the liver and spleen are the main target organs for cerium oxide, and liver, pancreas, and kidney for iron oxide NPs [39,40]. The size of NPs may also affect its distribution in different tissues, as 20 and 120 nm ZnO were mostly retained in the bone, kidney, and pancreas [41].…”
Section: Discussionmentioning
confidence: 99%